A medication review in the home can be revealing - Standage, Claire; Petty, Duncan; Wood, Su (Prescriber (London, England), 2015)
Medication non‐adherence may be well documented but lacks a definitive solution. One group of pharmacists in Bradford is attempting to tackle it with home visits.